Peace Corps Volunteers: Culture Shocks Encountered and Strategies to Overcome During Pre-Service Training in Indonesia - Fathor Rasyid (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
The purpose of the study is to examine the multifaceted reality of culture shocks experienced by Peace Corps Volunteers (PCV) during Pre-Service Training (PST) in Kediri, Indonesia and the strategies to overcome on a day to day basis. The research is descriptive in nature by semi-structured interviews and direct observation to PCV living in Kediri. The results of the research reveal that the culture shocks encountered are of three sorts: psychological, behavioral, and interpersonal communication change. Psychological change is of four kinds: using right-left hand, male-female interaction, asking personal privacy, and shake-hand. Moreover, the study also reveals three strategies to cope with culture shocks. They are self-confidence and optimism, accepting a new culture, and social support. It may be difficult to PCV to accept all differences with pleasure. However, a tolerant attitude and an open mind make them better to communicate with Community Liaison (CL). Eventually, by other people’s assistance, the PCV were able to encounter the culture shock.